ECONOMICAL EVALUATION BENTONITIC DEPOSITS OF UKRAINE USING METHOD OF REDUCTION COEFFICIENT - ANDRIEIEVA, O.; KURYLO, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article dedicated to economical evaluation bentonitic deposits of Ukraine. The evaluation was carried out using method of reduction coefficient. Quantity of resources, difficulties of geological structure were taken into consideration.